Water stable isotopes and volumetric discharge rates to monitor the Rhône water's seasonal origin. Issue 7 (July 2020) - Jean-Baptiste, Julien; Le Gal La Salle, Corinne; Verdoux, Patrick
Abstract: Along the 98 800 km 2 Rhône catchment area, 3 million people depend on the river resource and its sustainability. Flow rate monitoring of the French rivers showed the importance of the Swiss part of the Rhône (measured at station 1), the Isere (station 2) and the Durance rivers (station 3) contribution into the Rhône downstream (station 4) during summer when other recharges are decreasing. While their contribution is only of 10–30 % during most of the year, those rivers could contribute to more than 60 % of the Rhône flow rate during the driest period. The current study aims at confirming the key role of Alpine rivers contribution to the Rhône downstream flow by investigating an alternative monitoring tool of high-altitude water contribution. As a suitable tracer of latitude and altitude especially in a contrasted morphology, such as the Rhône watershed, water stable isotopes can be relevant to trace the origin of the recharge contributing to the waterflow. This study is based on a full hydrological cycle survey of the Rhône downstream water isotopes signature complemented by the current flow rate monitoring program of the Alpine rivers. With a linear regression model between both parameters data, the current study evidences the relevance of using water isotope signature to trace the seasonal change of water's origin and evaluate the high altitude waters contribution ( RQ AR ) into the Rhône river downstream flow rate (δ 2 H = 26.0 x RQAR – 57.9 with R = 0.88, R 2 = 0.79 and a p-value < 0.0001). It also confirms the key role of Alpine waters contribution to the Rhône River during summer with average value of 70 ± 6% and the importance to monitor the sustainability of their contribution in future drier period. Abstract : Rhône river; Alpine waters contribution; Volumetric discharge rates; Water stable isotopes; Climate change; Environmental management; Natural resource management; Isotope geochemistry; Geochemistry, Hydrology, Environmental science